HUBUNGAN FASILITAS, KUALITAS PELAYANAN, HARGA DAN TEMPAT TERHADAP KEPUASAN PENGUNJUNG AGROWISATA DI PT PERKEBUNAN TAMBI, KABUPATEN WONOSOBO - Idris Santoso; Hendrik Johannes Nadapdap (Hasanuddin University, 2019)
This research was purposed to identify the relationship among the facility, service quality, price and location toward the agrotourism visitors in Tambi Plantation Factory, Wonosobo Regency. The location was selected purposively (purposive) with a consideration that Tambi Plantation Factory was one of the biggest Private Plantation Factory which owned an agrotourism factor in Central Java Province. The research started from January to February 2019. This research was a quantitative descriptive research which done through survey. The sampling technique used in this research was non probality sampling by accidental sampling. The number of respondents involved in this research were 50 respondents of Tambi Tea Agrotourism visitors. The research result showed that facility (X1) had positive and medium level of relationship and significantly correlated to the visitor’s satisfaction (Y), service quality (X2) showed positive and strong level of relationship and significantly correlated to the visitor’s satisfaction (Y), and price (X3) had positive and medium level of relationship and not significantly correlated to the visitor’s satisfaction. Whereas location (X4) had low level of relationship and not significantly correlated to the visitor’s satisfaction (Y).